Fiscal Effects of the 1993 Colombian Pension Reform - Clavijo, Sergio (IMF Working Papers; Working Paper, 1998)
This study examines the fiscal impact of the pension reform adopted in Colombia in 1993, which established a fully funded, privately administered pension system alongside the existing pay-as-you-go state scheme. The reform increased the contribution rate and reduced the benefits of the state scheme. However, the fiscal cost of the reform was high, estimated at 1.5 to 2.3 percent of GDP annually over the next three decades. This reflects concessions made to special groups of public servants, the delay in making effective the new retirement conditions, and the minimum pension guarantee. A new generation of pension reforms needs to be adopted.